MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK MELALUI MEDIA PEMBELAJARAN - Alim Perangin-angin (JURNAL PENELITIAN FISIKAWAN, 2019)
Media as one component in teaching and learning activities is chosen on the basis of the objectives and learning materials that have been set. This study aims at finding the various benefits of using media in improving students’ learning activities. Therefore, educators as subjects of learning must be able to develop the right media, so that the learning material delivered can be accepted by students well. In addition, the media also has a function to overcome boredom and fatigue resulting from an educator's explanation that is difficult to understand. Educators must be able to determine or decide on the right media and in accordance with the subject matter so that the learning media will facilitate students in understanding the material presented.